World philosophies : an historical introduction - Cooper, David E. (David Edward), 1942- (Oxford, UK ; Cambridge, Mass. : Blackwell, 1996)
"From ancient philosophy to postmodernism, this new work is the most authoritative and up-to-date single-volume introduction to the history of Eastern and Western philosophy. These philosophical systems are viewed as attempts, above all, to provide integrated accounts of the place of human beings within the wider order of things, and to determine in the light of these philosophies the proper conduct of human life." "This timely and authoritative work will serve as the ideal introduction to philosophy, in all areas of the history of philosophy, Western and non-Western."--BOOK JACKET.
India -- China -- Greece -- Mediaeval philosophies -- Developments in Asian philosophy -- From Renaissance to Enlightenment -- Kant and the nineteenth century -- Recent non-Western philosophies -- Twentieth-century Western philosophies.
Includes bibliographical references (p. [483]-499) and index.
Keywords: Philosophy -- Introductions; Philosophy -- History; Philosophy -- Introductions